Seven-step framework to enhance practitioner explanations and parental understandings of research without prior consent in paediatric emergency and critical care trials. Issue 3 (29th August 2020) - Roper, Louise; Lyttle, Mark D; Gamble, Carrol; Humphreys, Amy; Messahel, Shrouk; Lee, Elizabeth D; Noblet, Joanne; Hickey, Helen; Rainford, Naomi; Iyer, Anand; Appleton, Richard; Woolfall, Kerry
Abstract : Background: Alternatives to prospective informed consent enable the conduct of paediatric emergency and critical care trials. Research without prior consent (RWPC) involves practitioners approaching parents after an intervention has been given and seeking consent for their child to continue in the trial. As part of an embedded study in the 'Emergency treatment with Levetiracetam or Phenytoin in Status Epilepticus in children' (EcLiPSE) trial, we explored how practitioners described the trial and RWPC during recruitment discussions, and how well this information was understood by parents. We aimed to develop a framework to assist trial conversations in future paediatric emergency and critical care trials using RWPC. Methods: Qualitative methods embedded within the EcLiPSE trial processes, including audiorecorded practitioner–parent trial discussions and telephone interviews with parents. We analysed data using thematic analysis, drawing on the Realpe et al (2016) model for recruitment to trials. Results: We analysed 76 recorded trial discussions and conducted 30 parent telephone interviews. For 19 parents, we had recorded trial discussion and interview data, which were matched for analysis. Parental understanding of the EcLiPSE trial was enhanced when practitioners: provided a comprehensive description of trial aims; explained the reasons for RWPC; discussed uncertainty about which intervention was best; provided a balanced description of trial intervention; provided a clear explanation about randomisation and provided an opportunity for questions. We present a seven-step framework to assist recruitment practice in trials involving RWPC. Conclusion: This study provides a framework to enhance recruitment practice and parental understanding in paediatric emergency and critical care trials involving RWPC. Further testing of this framework is required.